An electronically subsidized biomechanical model to study dynamic balance of head uppercut in boxing - Abd Elmwogud Abd Elazem, K. (Assiut Journal of Sport Science and Arts, 2014)
Super high performance of high levels' players represents a field of surprise and wonderings, which related to human performance and mechanical variables which happen in it, handled by those experts in kinetic performance development through make a connection between the main kinetic patterns, athletic skills and individual difference in performance as a basic for planning, training and teaching. (9:9) The balance considered a variable, one of mechanical features and main component in most sports activities, so, studying the main principles of balance and stability, considered one of topics which have a great importance in studying kinesiology and biomechanics, especially, in sport activities which requires revulsion in movements where the player loss balance and necessity of regain quickly this balance to start in new movement. (20:1) Balance in boxing has a special importance because it is one of sport activities which distinguished with speed and revulsion during offensive and defensive maneuvers which seem clearly in punches and free foot work or which followed by performing punch which requires transfer body centre of gravity to save balance where the boxer loss his balance and regain it one more time, so, balance can't achieved without a proper distance between boxer legs.